Dynamic output feedback H ∞ control problem for a class of linear neutral systems - Bariş Kizilsaç, Bayram (Elsevier BV, 2007)
Abstract This note presents the solution of dynamic output feedback H∞ control problem for a class of linear neutral systems in delay dependent case. First, sufficient conditions for the existence of such controllers is obtained by Lyapunov method in terms of linear matrix inequalities (LMIs). A parameterized characterization of the controllers is given in terms of feasible solutions to the certain matrix inequalities by using Matlab LMI Toolbox. Finally, a numerical example is given to illustrate the proposed results.